2007
DOI: 10.1118/1.2426407
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the focal spot size and shape for a medical linear accelerator by Monte Carlo simulation

Abstract: The focal spot size and shape of a medical linac are important parameters that determine the dose profiles, especially in the penumbral region. A relationship between the focal spot size and the dose profile penumbra has been studied and established from simulation results of the EGSnrc Monte Carlo code. A simple method is proposed to estimate the size and the shape of a linac's focal spot from the measured dose profile data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 17 publications
1
30
0
Order By: Relevance
“…The focal spot or source size is an important consideration in small fields (2). There are various methods to measure source size (47)(48)(49)(50), however it is beyond the scope of most clinical physicists. In such situation question lies as how sensitive is source size with respect to kΩ of a detector.…”
Section: Discussionmentioning
confidence: 99%
“…The focal spot or source size is an important consideration in small fields (2). There are various methods to measure source size (47)(48)(49)(50), however it is beyond the scope of most clinical physicists. In such situation question lies as how sensitive is source size with respect to kΩ of a detector.…”
Section: Discussionmentioning
confidence: 99%
“…6 for determination of Gaussian parameters of the focal-spot radiation profile and the extra-focal radiation profile using narrow and broad total focal radiation profiles measured by slits with two widths. Gaussian models of the focal-spot radiation profile and the extra-focal radiation profile based on experimental data are useful and necessary for Monte Carlo simulations for estimating accurate dose distributions at penumbral area [3]. If the focal radiation profiles were incorrect, the dose profiles at the penumbral area obtained by the Monte Carlo simulation could not be consistent with measured data.…”
Section: Discussionmentioning
confidence: 98%
“…Wang and Leszczynski [3] reported that the dose profile penumbra depends on the X-ray focal-spot size and shape. Therefore, if the focal-spot size became wider, the dose profile penumbra would be larger.…”
Section: Introductionmentioning
confidence: 99%
“…Test field B validates the primary focal spot size, shape, and location using the surrogate of penumbra 5 , 6 . Both the X and Y penumbra are evaluated.…”
Section: Methodsmentioning
confidence: 99%